Gone fishin' - Birnbaum, Roger; Sender, Julie Bergmen; Cain, Christopher (USA: Hollywood Pictures [production company] ; Kuala Lumpur : Berjaya HVN [distributor])
A funny thing happened on the way to the fishing hole in the hilarious comedy-adventure'Gone fishin'', which teams two Hollywood's most popular stars are lifelong pals who dream of catching'the big one' on a fishing trip to the Florida Everglades
Executive producer, Jill Mazursky Cody ; editor, Jack Hofstar
Cast: Joe Pesci, Danny Glover
Keywords: Comedy films; Adventure films; Sea in motion pictures